Participations of young Paraguayans in Argentine popular feminism (Polis (Santiago), 2023)
In dialogue with youth and feminist studies, this article seeks to understand the participation of Paraguayan youth in popular feminism in Argentina. Within a participatory, collective and feminist action research, I developed with them a face-to-face and digital ethnography in two popular neighborhoods of San Martín before and during the 2020 pandemic. Focusing on the intersection of gender with age and national origin, different subjectivities such as "young people", "women" and/or "migrants" emerged in their activism in the neighborhood. The study concludes that the participation of young migrants in feminist spaces, whether they are self-managed groups or social movements, is crucial to access rights that they lack in the country of origin. At the same time, through their incursion into popular feminism in the country of destination, they not only fight against the inequalities that afflict them, but also introduce new demands and meanings that dispute with academic feminisms.
Keywords: Youth; migration; women; activism; feminism